2010
DOI: 10.1007/s10562-010-0384-2
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Preparation Methods on the Performance of Metal Phosphate-Supported Gold Catalysts in CO Oxidation

Abstract: The influence of different preparation methods on the performance of metal phosphate-supported gold catalysts in CO oxidation was surveyed. A series of metal phosphate-supported gold catalysts (Au/M-P-O, M = Al, Ca, Fe, Zn, La, Eu, Ho) were prepared by depositing dodecanethiol-capped gold nanoparticles on the supports, or by using Au(en) 2 Cl 3 as the precursor, and these catalysts were tested in CO oxidation. The catalytic data were compared with the data obtained in our previous work employing catalysts prep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…In the literature, some metal carbonates, phosphates, and sulfates have been used as supports to load metals [2]. From the examples on the catalytic applications of metal phosphate-based catalysts cited in the Introduction section [4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, some metal carbonates, phosphates, and sulfates have been used as supports to load metals [2]. From the examples on the catalytic applications of metal phosphate-based catalysts cited in the Introduction section [4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,…”
Section: Resultsmentioning
confidence: 99%
“…Miura and co-workers [ 30 ] demonstrated that Pd/AlPO 4 showed high activity in the hydrogenation of naphthalene in the presence of CO. Takita and co-workers [ 31 ] employed Pt/AlPO 4 and Pt/CePO 4 -AlPO 4 for the hydrodechlorination of CHF 2 CClF 2 . More recently, Dai and co-workers [ 32 , 33 , 34 ] developed a series of metal phosphate-supported Au (denoted as Au/M-P-O, M = Fe, Co, Y, La, Pr, Nd, Sm, Eu, Ho, Er) catalysts and tested their performance in CO oxidation. Among them, Au/La-P-O and Au/Fe-P-O are representative catalysts, and the nature of active sites and reaction mechanisms were studied in detail [ 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…These catalysts were pretreated in O 2 -He at 300 or 500 °C because we found that as-synthesized Au/La-P-O (without any thermal pretreatment) was not active [86] when the reaction temperature was below 200 °C , due to the influence of the capping agents, whereas the pretreatment at 300-500 °C was sufficient to activate the Au/La-P-O catalyst. After testing all of these Au/M-P-O samples, we found that only Au/La-P-O was active for CO oxidation below room temperature [94]. Therefore, the activities of supported gold nanoparticles are not only related to the size of gold nanoparticles, but also influenced by the support and the preparation method.…”
Section: Au/metal Phosphatesmentioning
confidence: 97%
“…For Ag/Mg/TiO 2 , there is a combination of a curve with a maximum (at low temperatures) and an S-shaped curve (at high temperatures). This effect, caused by both supported silver [2,16] and gold [37,38,39,40,41] catalysts, is explained in the literature as due to the activity of small clusters and larger particles, at low temperatures and at high temperatures, respectively. It can be seen that light-off curves for as-prepared Ag/Ce/TiO 2 and Ag/Fe/TiO 2 samples are similar; consequently, the contents of active species in them were comparable (Figure 1).…”
Section: Resultsmentioning
confidence: 98%